2008
DOI: 10.1021/jp807753t
|View full text |Cite
|
Sign up to set email alerts
|

Energetic and Electronic Structure Analysis of Intrinsic Defects in SnO2

Abstract: Empirically, intrinsic defects in SnO2 are known to give rise to a net oxygen substoichiometry and n-type conductivity; however, the atomistic nature of the defects is unclear. Through first-principles density functional theory calculations, we present detailed analysis of both the formation energies and electronic properties of the most probable isolated defects and their clustered pairs. While stoichiometric Frenkel and Schottky defects are found to have a high energetic cost, oxygen vacancies, compensated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
208
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 315 publications
(229 citation statements)
references
References 51 publications
17
208
1
3
Order By: Relevance
“…This is shown for In 2 O 3 in Fig. 12 [170], but can also be seen in calculations of the electronic structure of the other TCOs [68,[171][172][173][174]. Such a band structure means that the Brillouin-zone-averaged band gap, and consequently also the CNL [175], are situated above the low-lying CBM, rather than within the fundamental band gap [63,167].…”
Section: Overriding Explanation?mentioning
confidence: 63%
See 2 more Smart Citations
“…This is shown for In 2 O 3 in Fig. 12 [170], but can also be seen in calculations of the electronic structure of the other TCOs [68,[171][172][173][174]. Such a band structure means that the Brillouin-zone-averaged band gap, and consequently also the CNL [175], are situated above the low-lying CBM, rather than within the fundamental band gap [63,167].…”
Section: Overriding Explanation?mentioning
confidence: 63%
“…In fact, its formation energy decreases with increasing Fermi level, making these especially important for typical Fermi level positions of n-type TCOs. However, such defects are acceptors [51,68], and so cannot contribute to this n-type conductivity. Rather, these defects may play an important role as compensating centres, limiting the attainable carrier densities and conductivities of TCOs.…”
Section: Cation Vacanciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Using density functional theory (DFT) calculations, it was found that oxygen vacancies (V O ) are the main cause of the (unintentional) n-type conductivity by forming shallow donor levels at the bottom of the conduction band with the mobility of electrons from Sn(II) to Sn(IV) sites in bulk SnO 2 [25], though other point defects such as Sn interstitial (Sn i ) and substitutional hydrogen impurities (H O ) play a certain role in the growth and processing environment [26,27]. This prediction was proved to be consistent with the experiment [28,29], and extended from bulk vacancy to surface oxygen vacancies at the SnO 2 surface [30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…It has good adsorptive properties and chemical stability. It can be deposited onto glass ceramics, oxides and substrate materials [1,2]. It has a high melting point and good transmission and does not easily react with oxygen and water vapor in the air, so it has a high specific volume and good cycling performance.…”
Section: Introductionmentioning
confidence: 99%